The effect of AI2Tio5 on electrical behavior of polymer-salt complexes / Fitriah Hassan - Fitriah, Hassan (2012)
In this study, aluminium titanate (Al2TiO5) has been prepared by the sol gel method. It has been intended for use as a ceramic filler in order to investigate how it affects conductivity and dielectric properties and also the nature of the complexes. Chitosan has been used as the host with ammonium thiocyanate (NH4SCN) as the salt to supply the conducting ions. Films of chitosan acetate (CA) , CA-NH4SCN complexes, CAAl2TiO5 complexes and CA-NH4SCN-Al2TiO5 complexes were prepared. The electrical conductivity of all samples has been calculated using the bulk resistance value obtained from the complex impedance plot in the frequency range between 50 Hz to 1 MHz. The film 60 wt.% chitosan – 40 wt.% NH4SCN system exhibits the highest room temperature electrical conductivity of 1.38 x 10-4 S cm-1. The highest electrical conductivity of the chitosan-NH4SCN-Al2TiO5 is 2.10 x 10-4 S cm-1 for the film containing 5 wt.% Al2TiO5 at room temperature, 25 oC. The modulus formalism indicates that the samples of chitosan-based electrolytes are ionic conductors. Infrared (IR) spectroscopy shows the occurrence of chitosan-salt complexation. X-ray diffraction (XRD) confirms that the Al2TiO5 filler sample with the highest electrical conductivity is the most amorphous. This is supported from the result of scanning electron microscopy (SEM). Hence the effect of Al2TiO4 filler is increment of conductivity and changing the degree of amorphousness of the highest conducting chitosan-NH4SCN system.